POLA PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR ISLAM TERPADU BUAH HATI SINTANG - Dike, Daniel; Parida, Lusila (STKIP Persada Khatulistiwa Sintang, 2024)
Special schools with a unique vision, curriculum and educational environment are very attractive to people in choosing education for their children. Sekolah Dasar Islam Terpadu Buah Hati Sintang is one of the attractions of the school with the greatest interest among the Sintang Muslim community. The aim of this research is to describe the pattern of multicultural education that occurs in Integrated Islamic elementary schools that combine two curricula. This research uses one case study research with qualitative data collection techniques. Data validity applied a process of triangulation of techniques and sources with inductive conclusion drawing. The research results show: (1) Sekolah Dasar Islam Terpadu Buah Hati Sintang has two curricula; the National curriculum and the Islamic curriculum, (2) The multicultural pattern developed is an expression of the integration of Malay and Javanese culture (mixed culture) but is patterned and developed in a strong Islamic spirit, (3) The curriculum process requires teachers and students to fulfill the dimensions and values of Islamic education as a whole, including Syakhsiyyah Islamiyyah, Tsaqofah Islamiyyah and Life Sciences. In order for the multicultural education dimension to take root in the educational process at Integrated Islamic Primary Schools, it is necessary to strengthen holistic pedagogy and peace education by combining 21st century skills capacities so as to increase the spirit of unity, brotherhood and solidarity at the internal and external levels of the educational unit.